Pemanfaatan E-Book Sebagai Sumber Belajar Terhadap Mahasiswa Universitas Efarina Pematangsiantar - Sihombing, Mifta Huljannah; Batubara, Abdul Karim; Abidin, Syahrul (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research is entitled "Utilization of E-Books as a Learning Source for Efarina University Students Pematangsiantar", this research aims to find out the benefits of using e-books in the learning process carried out by Efarina University students Pematangsiantar. In addition to the benefits, this study also aims to determine the obstacles or obstacles experienced by Efarina University students when using or accessing e-books. This research method uses a descriptive approach and qualitative research. And the result of this research is that the utilization of e-books is very effective and efficient in use by students, not only students, lecturers also use e-books as their learning resources.